Isomorphisms of spaces of affine continuous complex functions - Rondoš, Jakub; Spurný, Jiří (MATHEMATICA SCANDINAVICA, 2019)
Let X and Y be compact convex sets such that their each extreme point is a weak peak point. We show that ext X is homeomorphic to ext Y provided there exists a small-bound isomorphism of the space A(X,C ) of continuous affine complex functions on X onto A(Y,C ). Further, we generalize a result of Cengiz to the context of compact convex sets.